Supercritical Carbon Dioxide Extract of Seabuckthorn Leaves Enhances Rabies Virus Neutralizing Antibody Titers and CTL Response in Swiss Albino Mice - B Jayashankar; D Singh; KP Mishra; SN Madhusudana; Ashwin YB; SB Singh; L Ganju (Journal of Vaccines and Immunology - Peertechz Publications, 2016)
Introduction: Rabies is a viral disease that causes nearly thousands of death globally per year. Vaccination against rabies generates virus neutralizing antibodies and is the most successful and cost effective method of preventing the disease. In the present study, we have evaluated the adjuvant property of supercritical carbon dioxide extract (SCE) 300ET of Seabuckthorn (SBT) leaves against inactivated rabies virus antigen in Swiss albino mice. Methods: Mice were grouped as PBS control; inactivated rabies antigen (Rb) control; 300ET+Rb and Algel+Rb. All the mice were primed on day 1 followed by single booster at day 14. Sera were collected at different time points for RVNA analysis. Additionally, the effect of SCE on CD8+Granzyme B+ Cytotoxic T Lymphocyte (CTL) response, surface markers and cytokine levels were measured. Result: The results showed enhanced rabies virus neutralizing antibody (RVNA) titres using 300ET as compared to control and Algel groups as measured by Rapid Fluorescent Focus Inhibition Test (RFFIT). Moreover, the extract 300ET and Algel showed increased CD138+ (plasma cells) and CD11c+ (dendritic cells) cell population as compared to the inactivated rabies antigen immunized mice. The extract 300ET also stimulated cellular immunity by showing heightened CTL response and proinflammatory cytokines level such as TNF-α and IL-1β. Conclusion: Hence, our results suggested that SCE 300ET exhibits adjuvant activity by effectively enhancing antibody as well as cell mediated immunity in response to rabies antigen. Thus,SCE could be considered as a potential adjuvant candidate for rabies vaccines.